Rheumatoid Arthritis Treatment: Harnessing Novel Molecular Targets and Therapeutics for Improved Patient Outcomes - Maronese , Francesco; Alves, Maria Laura de Biasi; Mendonça , Juliana Coimbra de; Destefani , Afrânio Côgo; Destefani , Vinícius Côgo (Brazilian Journal of Implantology and Health Sciences, 2024)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that has significant unmet needs for improved treatment outcomes. This review provides an overview of emerging molecular targets and potential new therapies for managing RA. The discussed targets, such as CD40-CD40 ligand, programmed death protein 1 (PD-1), granulocyte-macrophage colony-stimulating factor (GM-CSF), interleukin-1 receptor-associated kinases (IRAKs), tyrosine kinase 2 (TYK2), bradykinin receptor 1 (B1R), and OX40-OX40 ligand, have shown promising results in preclinical studies and clinical trials. These findings stimulate continued efforts to develop more effective and safer therapeutic options, encouraging stakeholders to contribute to improving RA management.